Evaluating the Nutritional and Immune Potentiating Characteristics of Unfermented and Fermented Turmeric Camel Milk in Cyclophosphamide-Induced Immunosuppression in Rats - Thamer Aljutaily (MDPI AG, 2022)
Antioxidative, nutritional, and immune-boosting characteristics of turmeric-camel milk (TCM) and fermented turmeric-camel milk (FTCM) were investigated. A cyclophosphamide-induced immunosuppression rat model consisting of six experimental groups was carried out to study the effects of TCM and FTCM on weight gain, antioxidant status, immunoglobulin (Igs), pro-inflammatory and anti-inflammatory cytokines, and oxidative stress biomarkers. TCM or FTCM were orally administrated at 10 or 20 mL Kg−1 rat weight to CYP-immunosuppressed rats for 2 weeks in the presence of negative (NR) and positive (CYP) control groups. The phytochemical analysis and antioxidant capacity results indicated that TCM and FTCM contained considerable phenolic content with super antioxidant activities. CYP injection affected the rats' weight directly during the first week and then, a low weight gain percentage was recorded in treated groups at the end of the experiment. The most efficient treatment for recovering rats' weight was administering TCM and FTCM at 20 mL kg−1. Feed efficiency significantly increased with feeding TCM and FTCM in a dose-dependent manner. A significant improvement was found in WBCs, lymphocytes, and neutrophils count, suggesting that both TCM and FTCM alleviated the CYP-induced immunity suppression in a dose-dependent manner. IgG, IgA, and IgM concentrations in the CYP + TCM at 10 or 20 mL kg−1 and CYP + FTCM at 10 or 20 mL kg−1 groups were increased significantly. Concentrations of IL-1 beta, IL-6, IL-10, IL-13, and IL-TNF-α in the CYP group were significantly lower than in the NR group. Interestingly, both TCM and FTCM, especially with high doses, significantly enhanced cytokines production. Administrating FTCM was more potent than TCM, indicating that TCM with probiotics fermentation potentiated the immunological activity in immunosuppressed rats. Treated rats with TCM and FTCM can reverse CYP inhibition of antioxidant enzyme activities, significantly increase GSH, CAT, and SOD, and decrease MDA levels in a dose-dependent manner. In conclusion, these observations indicated that FTCM exhibits better improvements in weight gain, increased immune biomarkers in terms of WBCs, enhanced pro-inflammation and anti-inflammation responses, and accelerated antioxidant activity in immunosuppressed rats compared with TCM. It could be beneficial and profitable for boosting immunity and protecting against oxidative stress.